Development of Audiovisual-Based Teaching Materials for the Paduppa Anida Dance: Traditional Dance Learning in Junior High School - Sitti Hariati; Nurlina Sjahrir; Arifin Manggau (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Culturally grounded teaching materials remain scarce in secondary school dance education, and the transmission of the Paduppa Anida dance – a signature Bugis-Makassar welcoming dance created in 1965 – has been undermined by inconsistent movement variants circulating across community dance studios. This study develops, validates, and evaluates the effectiveness of an audiovisual teaching resource that reconstructs the dance's original repertoire for classroom use. A research and development (R&D) design following Thiagarajan's Four-D model (Define, Design, Develop, Disseminate) was employed. Movement material was reconstructed using Hawkins' exploration–improvisation–composition choreographic method and produced as a 9-minute, 720p audiovisual module. The product was reviewed by a dance-content expert and a media expert, then field-tested with Grade VII students (n = 20) at Junior High School 1 Makassar, Indonesia, in a limited trial (n = 6) followed by an extended trial (n = 15). The finding indicated that the product satisfied the Four-D development stages and achieved a mean expert-validated feasibility score of 87% (“very good” category) across both content and media dimensions. The extended field trial yielded a mean student-response score of 3.49 out of 4 (total score 787/900, “very good”), indicating gains in movement accuracy, learner confidence, and self-directed engagement relative to conventional instruction. The validated module offers teachers a standardized, reusable reference for authentic movement vocabulary and has been disseminated via YouTube to extend access beyond the classroom, supporting both in-class demonstration and independent student practice.